DEVELOPMENT AND PROBLEMS OF THE HEALTHCARE SYSTEM OF THE UZBEK SSR IN THE POST-WAR YEARS - Madaminov Ulug’bek Maxamadjon o‘g‘li (Bright Mind Publishing, 2025)
This paper examines the evolution of the healthcare system in the Uzbek Soviet Socialist Republic (SSR) between the 1950s and 1970s, a formative period marked by post-war reconstruction, institutional expansion, and state-led modernization. Drawing on historical records and Soviet health policy directives, the article outlines the development of medical infrastructure, personnel training, and disease prevention initiatives. It also explores the persistent structural challenges, including rural-urban disparities, shortages of skilled professionals, and bureaucratic inefficiencies. The findings contribute to a deeper understanding of the historical legacy of Soviet healthcare in Central Asia and its relevance to contemporary policy debates.
Keywords: Uzbek SSR, Soviet healthcare policy, medical infrastructure, public health, rural medicine, healthcare inequalities.